Sertifikasi Guru dalam Penguatan Profesional Guru MIN 49 Pidie - Tuti Fitria; Ammar Zainuddin; Masykur Masykur (LP3M IAI Al Urwatul Wutsqo Jombang, 2025)
Teacher certification is the process of granting formal credentials to educators as recognition of their competence and professionalism. Based on Law No. 20 of 2003 on the National Education System, teacher certification is mandatory to improve the quality of education. Certified teachers are expected to meet professional standards in teaching and classroom management. This study aims to analyze the professionalism of certified teachers at MIN 49 Pidie and evaluate the supervision process implemented. Using a qualitative descriptive method, data was collected through interviews, observations, and documentation. The results show that certified teachers at MIN 49 Pidie have improved in teaching creativity, the use of electronic media, and administrative management. Despite limited resources, teachers can implement more varied teaching methods. Additionally, academic supervision is conducted through lesson plan reviews, classroom observations, and individual meetings between the school principal and teachers to evaluate performance and provide professional development solutions. With effective certification and supervision, teachers are increasingly motivated to enhance their competencies through training and educational seminars.